Organizational Ambidexterity and Innovation: propositions for the advancement of theory and practice - Priscila Pagliarini Sartori; Ivan Lapuente Garrido (BBR: Brazilian Business Review)
This study addresses the relationship between organizational ambidexterity and innovation. It aims to present propositions for advancing theoretical and practical knowledge, in the face of different contextual conditions and the different industries in which organizations operate. By means of a narrative literature review, covering recent empirical studies, limits of knowledge in this field were identified, giving rise to propositions for its advancement, in theoretical and managerial aspects. As a first contribution, a systematization of the concepts and their relationships is presented, for the study of innovation as a result of the ambidextrous capacity, allowing a broad view of the field. Subsequently, four propositions are highlighted as contributions resulting from the study, based on contextual factors, such as the speed of changes in the environment, the transformation in business models and the leadership orientation towards innovation, given the diversity that characterizes each industry, capable of changing the balance between exploration and exploitation (E&E) over time in organizations.